2016
DOI: 10.1016/j.gca.2016.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Petrography and the REE-composition of apatite in the Paleoproterozoic Pilgujärvi Sedimentary Formation, Pechenga Greenstone Belt, Russia

Abstract: The first globally significant phosphorous-rich deposits appear in the Paleoproterozoic at around 2 Ga, however, the specific triggers leading to apatite precipitation are debated. We examine phosphorous-rich rocks (up to 8 wt% P 2 O 5 ) in 1.98-1.92 Ga old Pilgujärvi Sedimentary Formation, Pechenga Greenstone Belt, Russia. Phosphates in these rocks occur as locally derived and resedimented sand-to-gravel/pebble sized grains consisting of apatitecemented muddy sediments. Phosphatic grains can be subdivided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 61 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…Secondly, apatite is more likely than zircon to represent first-cycle detritus as it is prone to dissolution at source by acidic meteoric and pedogenic waters (Morton & Hallsworth, 1999). Despite being prone to dissolution at source (Joosu et al 2016) apatite is found in non-trivial abundance in nearly all Quaternary sediments (Nechaev & Isphording, 1993) and, because it is stable during diagenesis (due to the liberation of organic P and P adsorbed onto the surface of clay minerals; e.g. Bouch et al 2002), the detrital apatite signal is likely to be preserved once buried.…”
Section: A New Approachmentioning
confidence: 99%
“…Secondly, apatite is more likely than zircon to represent first-cycle detritus as it is prone to dissolution at source by acidic meteoric and pedogenic waters (Morton & Hallsworth, 1999). Despite being prone to dissolution at source (Joosu et al 2016) apatite is found in non-trivial abundance in nearly all Quaternary sediments (Nechaev & Isphording, 1993) and, because it is stable during diagenesis (due to the liberation of organic P and P adsorbed onto the surface of clay minerals; e.g. Bouch et al 2002), the detrital apatite signal is likely to be preserved once buried.…”
Section: A New Approachmentioning
confidence: 99%
“…Measurements of the REEs and Y in 2.5-3.7 Ga-old BIFs and metacherts (e.g., Bolhar et al 2004Bolhar et al , 2005Nishizawa et al 2005;Hofmann et al 2013) as well as in apatite (Lepland et al 2002;Nishizawa et al 2004;Joosu et al 2015Joosu et al , 2016Wudarska et al 2018) show that they contain "sea water fingerprints" with a Y anomaly and flat REE distribution patterns, identical to the pattern found in modern sea water (Elderfield and Greaves 1982). The Y anomaly seems to be present in geological records throughout the entire Precambrian, both after and prior to the great oxidation event (GOE) and up to the Eoarchean (Joosu et al 2015(Joosu et al , 2016Wudarska et al 2018). However, unlike modern seawater, the sedimentary rocks prior to the GOE are characterized by a lack of a negative Ce anomaly, which implies anoxic conditions (e.g., Lepland et al 2002;Joosu et al 2015Joosu et al , 2016Wudarska et al 2018), whereas a positive Eu anomaly indicates significant hydrothermal input into the Archaean oceans (Veizer et al 1989).…”
Section: Apatite Formation/transformation Pathwaysmentioning
confidence: 99%
“…The Y anomaly seems to be present in geological records throughout the entire Precambrian, both after and prior to the great oxidation event (GOE) and up to the Eoarchean (Joosu et al 2015(Joosu et al , 2016Wudarska et al 2018). However, unlike modern seawater, the sedimentary rocks prior to the GOE are characterized by a lack of a negative Ce anomaly, which implies anoxic conditions (e.g., Lepland et al 2002;Joosu et al 2015Joosu et al , 2016Wudarska et al 2018), whereas a positive Eu anomaly indicates significant hydrothermal input into the Archaean oceans (Veizer et al 1989). Due to the mafic melt differentiation rules, apatite crystallizes as one of the latest phases, and therefore they exhibit a negative Eu anomaly (Puchelt and Emmermann 1976).…”
Section: Apatite Formation/transformation Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations